Desarrollo ágil de una aplicación para dispositivos móviles. Caso de estudio: Taxímetro móvil - Babativa Goyeneche, Angélica María; Briceño Novoa, Paula Daniela; Nieto Lemus, Alba Consuelo; Salazar Morales, Omar (Ingeniería, 2016)
Context: Globalization has affected all productive sectors and in particular the software industry, which has required the development of new methodologies to suit the speed of the changes and allow quickly build products that meet the requirements of the customers. On the other hand, the GPS technology, 4G connectivity and integration of social networks that have the most current mobile phones have opened a large field of application, particularly in the area of the transport, mobility and citizen complaint, whose development can be successfully addressed through an agile methodology. Method: Agile methodology Scrum was used for the development of a mobile application on the Android operating system and GPS technology, which allows a Bogota taxi user to monitor the route and send a complaint to the social network Twitter in case of nonconformity. Some UML models were used for analysis and design of the application, and a confidence interval was used to validate the results. Results: Prototype of a mobile taximeter developed with an agile methodology that meets quality characteristics, extensibility and maintainability. T-student distribution was used to validate the measurement of the prototype on 50 samples, concluding that the difference between the measurement of a real taximeter and our mobile taximeter is on average 2 units with a standard deviation of 1,39 units. Conclusions: It is shown that with the agile development can be combined with UML modeling tools and statistical validation techniques for quality products that do not violate, but on the contrary, that reaffirm the agile development principles.